2002
DOI: 10.1111/j.1572-0241.2002.05843.x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in functional GI disorders: focus on constipation and resource utilization

Abstract: Constipation is common in the Canadian population and significantly impairs health-related quality of life. Poor quality of life is an important predictor of health care utilization in these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(146 citation statements)
references
References 25 publications
4
133
0
9
Order By: Relevance
“…For IBD patients, early diagnosis and aggressive intervention may reduce the possibility of complications (13) and significant delays in evaluation may therefore, lead to poorer outcomes (14) and an impaired quality of life (15). Constipation and diarrhea are also associated with significant impairment of quality of life (16)(17)(18), and delays in diagnosis and therapy are likely to impose a considerable burden on the individual and on society (3). The lengthened wait times for patients with suspected IBD, irritable bowel syndrome, chronic diarrhea and chronic constipation suggest that gastroenterologists prioritize consultations to deal more promptly with patients who should be seen urgently.…”
Section: Discussionmentioning
confidence: 99%
“…For IBD patients, early diagnosis and aggressive intervention may reduce the possibility of complications (13) and significant delays in evaluation may therefore, lead to poorer outcomes (14) and an impaired quality of life (15). Constipation and diarrhea are also associated with significant impairment of quality of life (16)(17)(18), and delays in diagnosis and therapy are likely to impose a considerable burden on the individual and on society (3). The lengthened wait times for patients with suspected IBD, irritable bowel syndrome, chronic diarrhea and chronic constipation suggest that gastroenterologists prioritize consultations to deal more promptly with patients who should be seen urgently.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is often associated with psychological symptoms of anxiety and depression and significant impairment in quality of life (Burnett, Whitehead, & Drossman, 1998;Irvine et al, 2002). Constipation is more common in women than men across the life span, and the prevalence rises with age, especially after middle age.…”
Section: Pelvic Floor Dyssynergiamentioning
confidence: 99%
“…A recent review estimated the overall prevalence of constipation in the US to be approximately 15% [4]. Recent studies have demonstrated that CC reduces patient's quality of life [5] and imposes a significant economic burden on the healthcare system [6].…”
Section: Introductionmentioning
confidence: 99%